A Study on Image Restoration and Deconvolution Techniques - Santhi, S (International Journal of Computer Sciences and Engineering, 2025)
Image restoration is the operation of taking a corrupted/noisy image and estimating the clean original image. Corruption may come in many forms such as motion blur, noise and camera misfocus. Deconvolution is an example of image restoration method. The deconvolution tries to invert the blurring of an image that is modeled by the convolution g = f*h+n. Blind deconvolution tries to do this without knowledge of the point spread function h that blurred the image. In this paper, different methods for image restoration viz. Deterministic Filter, Bayesian Estimation and iterative distribution reweighting (IDR) are discussed in detail